Factors influencing citizens' co-production of environmental outcomes: a multi-level analysis. Issue 11 (2nd November 2019) - Alonso, José M.; Andrews, Rhys; Clifton, Judith; Diaz-Fuentes, Daniel
ABSTRACT: Drawing on the literature on public service co-production, we examine the individual-level and local government-level factors associated with pro-environmental behaviours. Statistical analysis suggests that individuals that have high levels of self-efficacy, are more civically engaged or are carers, are more likely to 'co-produce' environmental outcomes. In addition, women, rural-dwellers, university graduates and middle-aged individuals exhibit more pro-environmental behaviours. Further analysis suggests that environmental co-production is more prevalent in areas with a high degree of compatibility between local public services and citizens, but worse recycling services and less overall investment in environmental services.